Psychosocial Professionals’ Perspectives and Practices Regarding Children Exposed to Intimate Partner Violence in Belgium’s French-Speaking Community - Nell Oger; Fabienne Glowacz (International Journal of Environmental Research and Public Health, 2026)
Despite growing evidence of the serious impact of intimate partner violence (IPV) on children, research on intervention practices in the psychosocial sector remains limited. This study investigates professionals’ perspectives on children exposed to IPV and how they address this issue in their practice. Using a sequential mixed-methods design, an online survey (N = 129) was followed by semi-structured interviews (n = 13). The findings reveal major limitations in interventions targeting children exposed to IPV, which help explain a significant gap between professionals’ perspectives—where children are recognized as victims of IPV and its substantial impact—and what is implemented in practice. In this context, children exposed to IPV often appear secondary both to children victims of other forms of abuse and to adult victims of IPV. Overall, these results underscore the need for specialized training and the development of targeted interventions to better address the specific needs of these children.